Pembelajaran Alat Musik Ritmis pada Siswa Kelas VII di SMP Negeri 2 Belitang Jaya Kabupaten OKU Timur - Irawan Sukma (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This study aims describe the preparation, implementation, and evaluation in Learning Rhythmic Musical Instruments for Grade VII Students at SMP Negeri 2 Belitang Jaya, East OKU Regency. The thing that wants to be examined is how the learning of rhythmic musical instruments for seventh grade students at SMP Negeri 2 Belitang Jaya can be conveyed well by the Cultural Arts Teacher, as evidenced by the ability of students to play rhythmic musical instruments. The descriptive qualitative method is very appropriate to use in this study. The results of this study indicate that the learning process of rhythmic musical instruments in class VII students has been classified as good, this is evidenced by many students who can play rhythmic musical instruments correctly and reach an average score of 85. Another factor is because it is supported by teaching strategies and musical abilities possessed by cultural arts teachers at SMP Negeri 2 Belitang Jaya is very good. In addition, the readiness of teachers in preparing learning tools in accordance with the 2013 Curriculum and other supporting facilities greatly supports the achievement of the objectives of rhythmic music learning.